The Influence of Good Corporate Governance on Financial Performance of Companies in Indonesia Using a Whistleblowing System - Christiawan, Yulius Jogi; Julian, Kelvin; Tarigan, Zeplin Jiwa Husada; Jie, Ferry (Journal of Ecohumanism, 2024)
Managers always strive to produce increased profitability by building systems in the company to be efficient and effective. Good corporate governance is formed in companies by increasing the role of supervise independent commission. This research aims to analyze the influence of good corporate governance on financial performance by using the whistleblowing system as a moderating variable. This research uses research samples from companies included in the LQ45. The research results state that good corporate governance with independent commissions positively affects financial performance. This condition can be seen from the increasing role and function of supervisors not affiliated with the company. Second, good corporate governance with an independent commission supported by the whistleblowing system can strengthen the impact of good corporate governance on financial performance. Third, the whistleblowing system established in companies has not been able to play a direct role in improving financial performance because there is still no system established in companies, and there are no government regulations to protect employees who disclose violations. Research provides practical contributions for governments and company managers to form adequate independent commissions because it can produce increased financial performance.